The Model of Natural Gas Market - Helnsky, Edward; Syifa Fatimah, Thalita; Millah Irsyaddin, Muhammad (Greenation Research & Yayasan Global Resarch National, 2023)
Playing a significant part in the Indonesian economy, the oil and gas industry serves as a vital source of state revenue and energy for various sectors, specifically fuel. Consequently, a study has been conducted to scrutinize the impact of crude oil prices on natural gas in Indonesia during the Covid19 pandemic. Using Kilian's (2009) innovative approach of crude oil price decomposition, the explanatory method has been adopted as the research methodology. The study includes four variables for both oil and natural gas market via a structural vector autoregressive model (SVAR). During the Covid-19 pandemic, it was discovered that the natural gas market in Indonesia is influenced by the crude oil market, but not because of changes in oil supply. The analysis showed that changes in demand played a larger role. As a result of the pandemic, the oil market became unpredictable, leading to an increase in natural gas prices as a substitute. Additionally, fluctuations in oil and gas prices were both affected by changes in demand in Indonesia during this time.